KADAR ASAM URAT PADA PASIEN TUBERKULOSIS DENGAN TERAPI OBAT ANTI TUBERKULOSIS (OAT) DI PUSKESMAS CEMPAKA MARET 2017 - Nafila Nafila; Rizqia Nurul Haqiqi; Sari Wahyunita (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that mostly attacks the lungs. Uric acid is the result of purine metabolism in the body. Actually, uric acid is a natural substance in the body but it becomes unnatural in the body when uric acid becomes up and beyond normal limits. The purpose of this study was to detemmine the description of uric acid levels in tuberculosis patients with anti tuberculosis drug therapy (OAT) at Puskesmas Cempaka. The population in this study was 22 patients with TB patiens who received OAT treatment. The sample of this research is 15 people with purposive sampling method. Examination was done in area of cempaka with capillary blood using rapid test method. Of the 15 patient studied with pulmonary tuberculosis who consumed OAT in Cempaka Puskesmas work area, obtained uric acid levels increased (26,67%) and normal levels uric acid (73,33%) in male gender (75%) and female gender (25%). Characteristics of age in the age group 41-50 years (25%), age 51-60 years (25%) In female gender. Should be monitored specifically for the symptoms of side effects of Anti Tuberculosis (OAT) by looking at clinical symptoms, such as nausea, vomiting, etc.